Emerging diagnostic challenges and characteristics of simian betaretrovirus infections in captive macaque colonies. Issue 4 (27th July 2017) - Yee, JoAnn L.; Grant, Richard; Van Rompay, Koen K.; Kuller, LaRene; Carpenter, Amanda; Watanabe, Robin; Huebner, Rebeca; Agricola, Brian; Smedley, Jeremy; Roberts, Jeffrey A.
Abstract: To better understand Simian betaretrovirus (SRV) seropositivity in virus‐negative macaques, we transfused blood from SRV‐infected or suspect donors into immunosuppressed naive recipients. Our results do not support typical SRV1‐5 infection as the cause, but provide evidence for several possibilities including serological artifact, new/different SRV, or an endogenous virus.